PERANCANGAN SISTEM INFORMASI PENDAFTARAN PASIEN BERBASIS WEB - Leonardy, Febiola; Arbainah; Lestari, Nurul Indah; Najwati, Zafira Ilmi (Equiva Journal, 2024)
The Patient Registration Information System (SIPP) was developed to make the registration process easier for patients quickly, practically and efficiently. As the number of patients increases, manual registration systems often face various obstacles such as slow administration processes, difficulties in searching for data, and the risk of damage or loss of documents. To overcome this problem, digitalization of web-based patient data management was implemented using Google Site. This system was designed using the Agile method using the Scrum framework, which allows developers to work flexibly, be adaptive to change, and produce features gradually through short iterations (sprints). In the design stage, UML diagrams such as use case diagrams, activity diagrams, ERD, and DFD are used to visualize user interactions, business process flows, and data structures in a structured manner. The final result of this research is a web-based patient registration system that is user-friendly, efficient, and capable of being integrated with other hospital information systems. The implementation of SIPP is expected to improve the quality of patient care, reduce data errors, and support more effective decision making in hospital management.